Integration of basal and apical embryo lineage regulators controls F-actin cable integrity and zygote asymmetry in Arabidopsis - Feng Xiong; Zhongjuan Zhang; Wen Gong; Marita Hermann; Deniz Tiambeng Bak; Frauke Garbsch; Thomas Laux (Proceedings of the National Academy of Sciences, 2025)
In many plants, the asymmetric division of the zygote sets up the apical–basal body axis. In the cress Arabidopsis , the zygote coexpresses regulators of the apical and basal embryo lineages, the transcription factors WOX2 and WRKY2/WOX8, respectively. WRKY2/WOX8 activity promotes nuclear migration, cellular polarity, and mitotic asymmetry of the zygote, which are hallmarks of axis formation in many plant species. However, the role of WOX2 and how the antagonistic WOX2 and WRKY2/WOX8 functions are integrated in the zygote have remained a long-standing question. Here, we report that WOX2 loss-of-function completely suppresses the reduced zygote asymmetry of wrky2 mutants and that WOX2 overexpression mimics the wrky2 phenotype. At the molecular level, WRKY2 downregulates WOX2 transcription in the zygote and the basal embryo lineage, in addition to promoting WOX8 expression. WOX2 antagonizes WRKY2 function by repressing WOX8 transcription. As a physiological readout, the WRKY2/WOX8-WOX2 balance regulates the integrity of F-actin cables in the zygote, providing a mechanistic framework for the role of WRKY2/WOX8-WOX2-mediated zygote asymmetry.